BEYOND DIRECT NUTRITION EDUCATION: THE GROWING IMPORTANCE OF POLICY, SYSTEMS, AND ENVIRONMENTAL CHANGE STRATEGIES IN THE USDA’S SNAP-ED PROGRAM - George Babu; Martha Ravola (Economy and Sociology)
The Supplemental Nutrition Assistance Program Education (SNAP-Ed) in the United States has undergone a significant evolution in recent years, shifting from the singular focus on direct nutrition education to a more comprehensive approach that incorporates policy, systems, and environmental (PSE) change strategies. This transformation reflects a growing recognition of the need for a multi-level, multi-sector approach to effectively address the complex issues of food and nutrition insecurity in diverse communities across the nation. The 2025 SNAP-Ed Plan Guidance issued by the United States Department of Agriculture (USDA) underscores this shift by placing increased emphasis on PSE interventions and community engagement. These new priorities aim to promote nutrition security and health equity on a broader scale, moving beyond individual behavior change to create supportive environments that make healthy choices more accessible and sustainable for SNAP-eligible populations. Successful PSE interventions implemented through SNAP-Ed have demonstrated significant potential for creating lasting, population-level changes in food environments and dietary behaviors. These strategies have shown promise in improving access to healthy foods, enhancing nutrition environments in schools and communities, and fostering collaboration among various stakeholders to address systemic barriers to healthy eating. The authors observe that meaningful community engagement and participation are crucial for ensuring that interventions are culturally appropriate, relevant, and sustainable. As SNAP-Ed continues to evolve, ongoing research and evaluation will be essential to refine PSE strategies and maximize their impact on nutrition security and health equity across diverse populations.